Investigating the prehistory of Tungusic peoples of Siberia and the Amur-Ussuri region with complete mtDNA genome sequences and Y-chromosomal markers. - Ana T Duggan (Public Library of Science (PLoS), 2013)
Evenks and Evens, Tungusic-speaking reindeer herders and hunter-gatherers, are spread over a wide area of northern Asia, whereas their linguistic relatives the Udegey, sedentary fishermen and hunter-gatherers, are settled to the south of the lower Amur River. The prehistory and relationships of these Tungusic peoples are as yet poorly investigated, especially with respect to their interactions with neighbouring populations. In this study, we analyse over 500 complete mtDNA genome sequences from nine different Evenk and even subgroups as well as their geographic neighbours from Siberia and their linguistic relatives the Udegey from the Amur-Ussuri region in order to investigate the prehistory of the Tungusic populations. These data are supplemented with analyses of Y-chromosomal haplogroups and STR haplotypes in the Evenks, Evens, and neighbouring Siberian populations. We demonstrate that whereas the North Tungusic Evenks and Evens show evidence of shared ancestry both in the maternal and in the paternal line, this signal has been attenuated by genetic drift and differential gene flow with neighbouring populations, with isolation by distance further shaping the maternal genepool of the Evens. The Udegey, in contrast, appear quite divergent from their linguistic relatives in the maternal line, with a mtDNA haplogroup composition characteristic of populations of the Amur-Ussuri region. Nevertheless, they show affinities with the Evenks, indicating that they might be the result of admixture between local Amur-Ussuri populations and Tungusic populations from the north.